The impact of female misuse of power on their families in two selected plays by Clifford Odets and Edward Albee - Kadhim, Rawaa Jawad (Research Journal in Advanced Humanities, 2023)
The following study investigates the impact of powerful women in the two American plays Awake and Sing! by Clifford Odets and The American Dream by Edward Albee .The study directs our attention towards the significant role of powerful female characters in the deterioration of familial structures and the dissolution of interpersonal connections during the 20th Century. They were portrayed as authoritative and commanding individuals. They asserted their entitlement to express anger, wit, and ruthlessness. Their dominion was evident in their capacity to dictate the lives of others, regardless of the ramifications it had on those directly entangled with them. The study posits that Foucault’s analysis of power presents a unique interpretation that has the capacity to provide valuable insights into the essence of power in the two plays. It commences by offering an explication of the American family, and subsequently concludes by delineating certain resemblances between the chosen plays, drawing upon Foucault’s conceptualization of power.